Modelling of Hysteresis in Vibration Control Systems by means of the Bouc-Wen Model - Chia-Ming Chang; Salvatore Strano; Mario Terzo (Shock and Vibration)
The review presents developments concerning the modelling of vibration control systems with hysteresis. In particular, the review focuses on applications of the Bouc-Wen model that describes accurate hysteretic behaviour in vibration control devices. The review consists of theoretical aspects of the Bouc-Wen model, identification procedures, and applications in vibration control.